Developing a Fairy Tale Book with a Theo-Centric Approach to Optimize the Honest Character of Elementary School Students - Harahap, Siti Mandasari (Jurnal Pendidikan Profesi Guru, 2026)
This study aims to develop a fairy tale book based on the Theo Centric approach as a character learning medium to optimize the honesty value of elementary school students. The background of the study stems from the need to strengthen character education integrated in teaching materials that are interesting, easy to understand, and able to internalize religious values ​​​​meaningfully. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of needs analysis, design, development of a fairy tale book prototype, implementation in fourth grade students, and evaluation of effectiveness. Participants consisted of 32 students and one class teacher. The research instruments included an expert validation sheet, student and teacher response questionnaires, and an honest character test. The results showed that the Theo Centric fairy tale book obtained an expert feasibility score of 92% (very appropriate) and a student readability level of 88%. The implementation of the book increased the honest character score from an average of 68 to 87, indicating an increase of 19 points. This study implies the importance of using teaching materials based on divine values ​​​​packaged in narrative to encourage honest behavior in students, while also providing an alternative model for teachers in character education.